Cost-Effectiveness Analysis of Insulin Therapy in Patients with Type 2 Diabetes Mellitus (The research was conducted at dr. Iskak Tulungagung Hospital) - Putri, Nadhifa Maharani Mega Mulya; Hidayati, Ika Ratna; Atmadani, Rizka Novia; Muzayyanah, Binti (Pharmaceutical Journal of Indonesia, 2026)
Introduction: Diabetes mellitus is a series of metabolic diseases with signs of hyperglycemia arising from problems with insulin secretion or both. The cost of treating diabetes mellitus was estimated at USD 727 billion in 2017 and is expected to increase every year. The variation in antidiabetic drugs will lead to variation in cost and success rate. Objectives: Therefore, cost-effectiveness analysis, also known as method rate analysis, is used to determine the method that has the lowest cost and is effective to achieve the same goal. Objectives: The purpose of this study was to determine the cost-effectiveness of insulin therapy in patients with type 2 diabetes mellitus hospitalized at RSUD dr. Iskak Tulungagung Regency in 2023. Methods: The method used was a descriptive non-experimental approach, with a cross-sectional design and the instrument used was a retrospective data collection sheet at RSUD dr. Iskak Tulungagung Regency totaling 74 patients. Results: The results and conclusions of this study are the use of Single Insulin with GDS and GDP parameters that have low costs (cost-effective) is Insulin Novorapid® (Insulin Aspart) with an ACER value of Rp. 283,899.23 and the average direct medical costs incurred are Rp. 14,194. 961.25, while the use of combined insulin with RPG, 2-h PG and FPG parameters that have low costs (cost-effective) is the combination of Novorapid® (Insulin Aspart) + Levemir® (Insulin Detemir) with an ACER value of Rp. 412,230.56 and the average direct medical costs incurred are Rp. 18,177,082.66. Conclusions: Novorapid® as single insulin and Novorapid® + Levemir® as combination insulin are cost-effective.